2017
DOI: 10.1111/imj.13644
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting insulin immunoassays during investigation of apparent spontaneous hypoglycaemia and insulin overdose

Abstract: We report two cases of hypoglycaemia; one with apparently spontaneous hypoglycaemia and one with presumed insulin overdose. In both cases insulin concentration was normal when measured with the Roche immunoassay, but elevated when remeasured with the Advia Centaur immunoassay and a diagnosis of hypoglycaemia secondary to insulin analogue administration was made. These cases highlight that physicians need to understand the binding characteristics of the insulin immunoassay they use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In 2001 Sapin et al [ 13 ] first suggested the absence of cross-reactivity with insulin analogues in some assays [ 13 ], which was subsequently confirmed by other groups [ 12 , 14 16 ]. There are also a number of publications with clinical cases on this topic [ 17 20 ]. Chemmanam et al [ 20 ] reported two cases of hypoglycemia where the diagnosis was initially unclear due to the use of the RE assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2001 Sapin et al [ 13 ] first suggested the absence of cross-reactivity with insulin analogues in some assays [ 13 ], which was subsequently confirmed by other groups [ 12 , 14 16 ]. There are also a number of publications with clinical cases on this topic [ 17 20 ]. Chemmanam et al [ 20 ] reported two cases of hypoglycemia where the diagnosis was initially unclear due to the use of the RE assay.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases insulin concentration was normal when measured with the Roche’s immunoassay, but was appropriately elevated when remeasured with the Advia Centaur immunoassay and a diagnosis of hypoglycemia secondary to insulin analogue administration was made. In addition, this work compared 4 analytical platforms with respect to the detection of 5 insulin preparations [ 20 ]. These cases emphasize that understanding the binding characteristics of the insulin immunoassay used by the laboratory is essential to making a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 During laboratory research, exogenous injection of human insulin is characterized by high levels of this hormone, as well as suppression of C-peptide and proinsulin. 10 However, in cases of surreptitious injection of insulin analogs, many authors 2,[11][12][13] reported the low level of detected insulin. Some experts have linked these cases to low cross-reactivity of several types of immunoassay with insulin analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Some experts have linked these cases to low cross-reactivity of several types of immunoassay with insulin analogs. 2,11,12,[14][15][16][17] This is due to differences in immunoreactivity of insulin analogs and human insulin because of amino acid sequence changing in the C-terminal part of the B-chain. 11 Moreover, changing of only 1 amino acid can highly decrease the ability of some analyzers to observe this preparation.…”
Section: Introductionmentioning
confidence: 99%